Quasi-static analysis of composite slab - Abdullah, Redzuan; Poton-Cole, Vidal P.; Samuelm Easterling, W. (Faculty of Civil Engineering, Universiti Teknologi Malaysia, 2007)

(untitled)
This paper presents a method for modeling and analyzing steel deck-concrete composite slabs to obtain quasi-static response using non-linear dynamic finite element analysis. A three-dimensional finite element model of steel-concrete composite slab was developed and analyzed using ABAQUS/Explicit module software. The main considerations included in the model were tensile brittle cracking of concrete, horizontal shear bond behaviour between the concrete and the steel deck and the analysis control. The horizontal shear bond characteristic of the slab model was deduced from bending test data. The finite element modelling and analysis method presented here for composite slabs which failed by a combination of concrete tensile brittle cracking and horizontal shear slip described here was found to be accurate compared to bending test data.